2001
DOI: 10.1263/jbb.91.339
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Chitinous Wastes to Hydrogen Gas by Clostridium paraputrificum M-21.

Abstract: The chitinolytic bacterium Clostridium paraputrificum strain M-21 produced 2.2 and 1.5 mol hydrogen gas from 1 mol N-acetyl-D-glucosamine (GlcNAc) and ball-milled chitin equivalent to 1 mol of GlcNAc, respectively, at pH 6.0. In addition, strain M-21 efficiently degraded and fermented ball-milled raw shrimp and lobster shells to produce hydrogen gas: 11.4 mmol H2 from 2.6 g of the former and 7.8 mmol H2 from 1.5 g of the latter. Hydrogen evolution from these shell wastes were enhanced two fold by employing aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…AAD with formation mainly of acetic and butyric is normally one of the most efficient ways for bio-hydrogen production especially by Clostridium sp. (Evvyernie et al, 2001). The rest of VFAs determined (propionic, valeric and heptanoic) were detected always in very low concentrations for all the SRTs tested.…”
Section: Evolution Of Volatile Fatty Acids (Vfas)mentioning
confidence: 84%
“…AAD with formation mainly of acetic and butyric is normally one of the most efficient ways for bio-hydrogen production especially by Clostridium sp. (Evvyernie et al, 2001). The rest of VFAs determined (propionic, valeric and heptanoic) were detected always in very low concentrations for all the SRTs tested.…”
Section: Evolution Of Volatile Fatty Acids (Vfas)mentioning
confidence: 84%
“…Higher rates of fermentative H 2 production have been reported with a consortium of mesophilic or hyperthermophilic bacteria in optimized bioreactors [54,55]. Depending on the bacterial species and organic nutrients employed, such fermentations result in the generation of an abundance of small organic acids, such as malate, lactate, propionate, butyrate, and/or acetate [41,[56][57][58][59][60][61][62]. The further conversion of these small organic acids to H 2 is not an energetically favorable reaction and cannot be supported by the fermentative metabolism of the anaerobic bacteria.…”
Section: Hydrogen Production By Anaerobic Fermentative Bacteriamentioning
confidence: 99%
“…Most of the studies were carried out on glucose as a substrate. However it has been reported that many other organic substrates, such as inulin [20], sucrose [16,21], acetylglucosamine and chitin [22], wastestreams containing xylose [23], lignocellulosic waste [24] and even wastewater sludge [4], are potential sources for hydrogen production. According to our knowledge, lactose as the sole carbon source for hydrogen production has never been reported.…”
Section: Hydrogen Productivity By Other Organisms On DI Erent Substratesmentioning
confidence: 99%